Energizing Economic Growth in Ghana : Making the Power and Petroleum Sectors Rise to the Challenge - World Bank (Washington, DC, 2013)
The main objective of this report is to provide the new Government of Ghana with recommendations on the actions needed to improve the performance of Ghana's energy sector. The report focuses on the power and petroleum sectors, taking account of the interdependence between the sectors, and providing recommendations for how they can, together, drive future economic growth. This report aims to highlight the centrality of fixing the problems in the power sector as a path to ensuring that Ghana's economic growth ambitions are not stymied by a lack of electricity. The problems and their solutions are well known; what has been lacking is decisive and timely decision making to break the tendency to adopt reactive measures that often come too late when proactive measures will have led to better outcomes. Demand for gas in the power sector is set to expand rapidly, as new thermal generation capacity is built to meet rapidly growing power demand. However, to ensure successful development of its gas sector, Ghana will need to address a number of important challenges. The paper is organized as follows: chapter one gives introduction; chapter two deals with electricity demand and supply; chapter three deals with resolving generation and transmission bottlenecks; chapter four gives reforms urgently needed in power distribution; chapter five focuses on natural gas sector; and chapter six focuses on upstream oil and gas sector.